Faktor-Faktor yang Mempengaruhi Resiliensi Warga Binaan Pemasyarakatan Pria: Studi Literatur - Yunita Anggerina Koroh; Megah Andriany (Holistic Nursing and Health Science, 2020)
Introduction: Resilience has an important role for psychological balance of male inmates as a population which is more vulnerable to a decline in mental health. This is a descriptive qualitative study with a literature review research design. Methods: This study was a literature review by examining ten literatures that had passed the screening process according to the specified inclusion criteria. Results: The results of this study found that there are two factors which affecting the resilience of male inmates, namely protective factor and risk factor. The protective factors are internal factors: social competence and good self-acceptance; and external factor named social support. The risk factors are internal factor in the form of psychological character: impulsivity and external factor from the family namely history of childhood trauma. The resilience of male inmates is affected by two factors consisting of protective factors and risk factors. The protective factors contribute to the high resilience level and the risk factors contributes to the low resilience level of male inmates).